2017
DOI: 10.18632/oncotarget.23695
|View full text |Cite
|
Sign up to set email alerts
|

Exon 3 mutations ofCTNNB1drive tumorigenesis: a review

Abstract: The canonical Wnt/β-catenin signaling pathway, an important modulator of progenitor cell proliferation and differentiation, is highly regulated for the maintenance of critical biological homeostasis. Decades of studies in cancer genetics and genomics have demonstrated that multiple genes encoding key proteins in this signaling pathway serve as targets for recurrent mutational alterations. Among these proteins, β-catenin and adenomatosis polyposis coli (APC) are two key nodes. β-catenin contributes in transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 184 publications
(186 reference statements)
4
140
0
Order By: Relevance
“…As reported by previous studies, the majority of deleterious alterations in the CTNNB1 gene were restricted to the serine/threonine phosphorylation sites T41 and S45. In our study, T41A (n = 111/204; 54.4%), S45F (n = 40/204; 19.6%) and S45P (n = 18/204; 8.8%) were the most frequent amino acid exchanges affecting sites involved in the modulation of the interaction of β-catenin with several kinases: Sequential phosphorylation at T41, S33 and S37 is mediated by the glycogen synthase kinase 3 beta (GSK-3β), while S45 is phosphorylated by the casein kinase-1 alpha (CK1α) targeting β-catenin for ubiquitination and subsequently proteasomal www.nature.com/scientificreports www.nature.com/scientificreports/ degradation 5,22,23 . Mutations affecting these phosphorylation sites lead to stabilization and translocation of β-catenin into the nucleus where it acts as a transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by previous studies, the majority of deleterious alterations in the CTNNB1 gene were restricted to the serine/threonine phosphorylation sites T41 and S45. In our study, T41A (n = 111/204; 54.4%), S45F (n = 40/204; 19.6%) and S45P (n = 18/204; 8.8%) were the most frequent amino acid exchanges affecting sites involved in the modulation of the interaction of β-catenin with several kinases: Sequential phosphorylation at T41, S33 and S37 is mediated by the glycogen synthase kinase 3 beta (GSK-3β), while S45 is phosphorylated by the casein kinase-1 alpha (CK1α) targeting β-catenin for ubiquitination and subsequently proteasomal www.nature.com/scientificreports www.nature.com/scientificreports/ degradation 5,22,23 . Mutations affecting these phosphorylation sites lead to stabilization and translocation of β-catenin into the nucleus where it acts as a transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin is a protein encoded by CTNNB1 and appears to be a key downstream effector of the Wnt pathway for regulating cell growth/survival [3]. This pathway is activated by genetic mutations including CTNNB1 exon 3 and adenomatous polyposis coli (APC) protein, that stabilize the β-catenin protein which accumulates in the cytoplasm and then translocates to the nucleus [4].…”
Section: Introductionmentioning
confidence: 99%
“…The result of the change includes increased cell proliferation, enhanced immunosuppression, and disruption of metabolic regulation. 54 Reports suggested that mutations in APC can also correlate with high expression levels of CTNNB1, whereas wild-type APC expression can reduce CTNNB1 levels in CRC cells. 55,56 Irrespective of the expression level of this gene, it is regarded as an important indicator of malignancy.…”
Section: Discussionmentioning
confidence: 99%